'Indigenous Knowledge' and 'Science' in the Age of Globalization. (January 2014) - Ramnath, Aparajith
Globalization accentuates the local, as seen in the increasing emphasis on 'indigenous knowledge' in the discourse of governments, universities and international organizations. This essay explores the categories of 'indigenous knowledge' (IK) and 'science'/ 'Western science' (WS) as used by scholars in science policy, anthropology and the history of science, and examines how the similarities and differences between IK and WS have been understood. It argues that IK is an imprecisely formulated term, and highlights recent scholarship that sees IK and WS as constructed categories that emerged in particular historical circumstances. It concludes by discussing briefly the notion that these mutually exclusive labels should be avoided, so as not to privilege some forms of knowledge over others.